Правові аcпекти діяльності іноземних адвокатів у країнах Європейського Союзу: на прикладі Німеччини - Кравчук, В.; Kravchuk, V. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті проаналізовано умови набуття правого статусу адвоката іноземцями в Німеччині і обмеження, що стосуються ведення власної канцелярії такими адвокатами. Іноземець, що здійснює адвокатську діяльність, повинен вступити до адвокатської палати та бути зареєстрованим в суді у списку адвокатів. Після допуску до здійснення адвокатської діяльності, внесення до списку в німецькому суді, професійна позиція іноземного адвоката зрівнюється з позицією німецького адвоката. The terms of acquisition of legal status of advocate by foreigners in Germany and limitations that touch the conducting of professional activities by such advocates are analysed in the article. A study of experience of countries of Central and Eastern Europe in the questions of realization of advocate practice in the separate countries-members of EU is very actual. A foreigner who carries out advocate activity must enter the advocate chamber and must be registered in a court in the list of advocates. Carrying out the professional activity, he can allude to membership in the German advocate chamber. After admitting to realization of advocate activity, professional position of foreign advocate is evened with position of the German advocate. The right on the German professional title is given after handing over of qualifying examination or at presence of three-year work experience in the sphere of the German law. Although requirements to the person, who wishes to be engaged in advocate practice, are relatively simple, in practice facts of admittance of advocates from the countries of Central Europe are single.
Legal Aspects of Foreign Advocates Activities in the Countries of European Union: on the Example of Germany.
Keywords: правовий статус; адвокат; адвокатська діяльність; суд; legal statust; advocate; advocate activity; cour